Politics and social partnership: flexible network governance - Hardiman, Niamh (Economic & Social Studies, 2006)
This paper reassesses the relationship between social partnership and the broader Irish policy process. What has developed may be conceptualised as ?flexible network governance?. While pay regulation may be less strongly institutionalised than in other countries with national-level pay deals, social partnership has created networks for establishing and maintaining priorities that matter to those involved in the process. These have not replaced conventional methods of developing policy. Nor do they displace government prerogative: politics can trump partnership. Social partnership is open to some criticism on grounds of both effectiveness and legitimacy. But is has proven robust to date on the core issues it deals with.
This paper was delivered at a conference ?Social Partnership: A New Kind of Governance?? funded by the Irish Research Council for the Humanities and Social Sciences, National Institute for Regional and Spatial Analysis and the Department of Sociology, NUI Maynooth, 14-15 September 2004.
Keywords: Social partnership; Governance; Ireland; Policy process